A Model for Reliability Estimation Using Inter Failures Time Data - ThirumalaiSelvi, R; Gayathry, G (International Journal of Computer Sciences and Engineering, 2025)
Software reliability models is the best choice to monitor reliability of software process. These methods aid the software development team to identify the necessary actions that are carried out during software failure process. The present work attempts to develop a new model to check the software reliability by incorporating the failure rate of both hardware as well as software. The proposed new model based on time between failures observation, which is based on Non-Homogeneous Poisson Process (NHPP). Maximum Likelihood Estimation (MLE) method applied to determine the unknown parameters of the model